Effect of hydrostatic pressures on the superconductivity of new BiS2 based REO0.5F0.5BiS2 (RE=La, Pr and Nd) superconductors. (September 2015) - Jha, Rajveer; Kishan, H.; Awana, V.P.S.
Abstract: We study the effect of hydrostatic pressure on superconductivity of new BiS2 based layered REO0.5 F0.5 BiS2 (RE=La, Pr, and Nd) compounds through the measurements of dc electrical resistivity. The REO0.5 F0.5 BiS2 (RE=La, Pr and Nd) compounds synthesized by solid state reaction route via vacuum encapsulation are crystallized in the tetragonal P4/ nmm space group. At ambient pressure the superconducting transition onset temperatures ( T c onset ) are 2.7 K, 3.5 K and 4.5 K, which are enhanced substantially under external hydrostatic pressure to 10.5 K, 7.8 K and 7.5 K for LaO0.5 F0.5 BiS2, PrO0.5 F0.5 BiS2 and NdO0.5 F0.5 BiS2 respectively at 1.68 GPa. The normal state electrical resistivity decreases with applied pressure for REO0.5 F0.5 BiS2 (RE=La, Pr and Nd). The electrical resistivity under magnetic field and applied pressure has been measured to estimate upper critical field H c2 (0), the values of which are 15.9 Tesla, 8.8 Tesla and 8.2 Tesla for LaO0.5 F0.5 BiS2, PrO0.5 F0.5 BiS2 and NdO0.5 F0.5 BiS2 compounds. Substantial enhancement of superconductivity under moderate pressures in studied new BiS2 based superconductors call for the attention of condensed matter physics community. Highlights: New superconductor REOFBiS2 . Impact of hydrostatic pressure on superconductivity. Hydrostatic pressure induced significant enhancement in superconductivity.